Attitudes, Perceptions, and Barriers to Research and Publishing Among Research and Teaching Staff in a Nigerian Research Institute - Okoduwa, Stanley I. R.; Abe, James O.; Samuel, Blessing I.; Chris, Aimee O.; Oladimeji, Richard A.; Idowu, Olanipekun O.; Okoduwa, Ugochi J. (Frontiers in Research Metrics and Analytics, 2018)
The economic development of any nation is centered on research. Unfortunately, research activities had suffered serious setback in tertiary research institutions in Nigeria. This study explores the attitudes, perceptions and barriers to research and publishing among academic staff in Nigerian Institute of Leather and Science Technology, (NILEST) Zaria Nigeria. A structured self-administered questionnaire was distributed among 130 research and teaching staff at the various Directorates in NILEST. Data are presented in frequencies and percentages for questionnaire responses. Exactly 93.85%of the questionnaires were validated for the study which included 81.15% male and 18.85% female. The participant were researchers (26.23%), lecturers (31.15%), Technologist (20.49%) and Instructors (22.13%). The majority of participant agreed that research is important for the institute (90.98%). A total of 81.15% believed that conducting research should be mandatory for all academic staff. Only 44.26% was self-reported to have ongoing research. Some of the obstacles reported to have prevented research activities included: lack of funding (72.13%), lack of professional mentorship (84.43%) and inadequate research facilities (89.34%). Participants without a single published paper were 54.545%. Some of the reasons given for not having published papers were “no writing experience (95.65%), high publishing fee (79.71%) and long waiting period for peer review (97.10%)”. The suggestions to improve research status by respondents included“ provision of research grants/funds (92.62%), provision of internet facilities (95.10%), mandatory publication (26.23%) and appropriate mentorship (34.43%). Majority of the respondents believed that research is relevant, only a few were engaged in active research and published articles as evidence. It is therefore recommended that policy makers should devise strategies to focus on active research activities in order to achieve the desire research mandate and goal of institutions in the development of the nation’s economy.